حماية المزكي ماله بزكاته - اليوسف، أحمد بن عبدالله بن محمد (جامعة القصيم, 2012)
لا يجوز دفع الزكاة إلى الوالدين والمولودين من سهم الفقراء والمساكين في حال وجوب نفقتهم على الدافع بالإجماع.\ 2- يجوز دفع الزكاة إلى الوالدين والمولودين من سهم الفقراء والمساكين في حال عدم وجوب نفقتهم عليه.\ 3- - يجوز دفع الزكاة إلى الوالدين والمولودين من غير سهم الفقراء والمساكين.\ 4- لا يجوز للزوج دفع زكاة ماله إلى زوجته إجماعاً.\ 5- يجوز للزوجة أن تدفع زكاتها إلى زوجها.\ 6- يجوز دفع الزكاة إلى أقاربه كالأخوة والأعمام وأولادهم، بشرط عدم وجوب نفقتهم عليه، وعدم إرثه منهم، ما داموا من المستحقين لها.\ 7- يجوز قضاء دين الميت من الزكاة إذا كان الدين بسبب مباح.\ 8- لا يجوز للدائن أن يسقط دينه عن مدينه الفقير المعسر ويحسبه من زكاة ماله.\ 9- لا يجوز بذل زكاة ماله فيما يشرع فيه التقرب إلى الله. كشراء الأضحية أو إخراج الكفارة الواجبة، أو نفقة الحج، وكذلك لا يجوز صرف الزكاة في تكاليف استقبال الضيوف والعزائم.\ 10- المشاركة في دفع الدية أو عونه الزواج من الزكاة، فيها تفصيل مذكور في البحث.\ 11- المشاركة في الأعمال الخيرية من الزكاة، فيه تفصيل مذكور في البحث.\ 12- لا يجوز احتساب الضريبة، وقسائم المخالفات، وقسط التأمين من الزكاة.\ 13- أن القائمين على تحصيل الزكاة وتوزيعها في العصر الحاضر من الأشخاص التابعين للجمعيات الخيرية المصرح لها من قبل الحكومة، ينطبق عليهم وصف العاملين عليها الوارد في سورة التوبة في آية أهل الزكاة. وهؤلاء يعطون من الزكاة، بشروط مذكورة في البحث. وهذا يشمل الرجال والنساء في الراجح من أقوال أهل العلم وهذا فيمن لا يتقاضى راتباً من الدولة مقابل عمله. والله أعلم. 1-\ It is not permissible to pay Zakat (obligatory charity) to parents and children of the payer from shares of the poor and needy if the payer is required to pay their expenses, (as the position of the consensus of Islamic scholars)\ 2-\ It is permissible to pay Zakat to parents and children of the payer from shares of the poor and needy if the payer is not required to pay their expenses.\ 3-\ It is permissible to pay Zakat to parents and children of the payer from shares of other than the poor and needy portion.\ 4-\ It is not permissible for a husband to pay Zakat to his wife, (as the position of the consensus of Islamic scholars)\ 5-\ It is permissible for a wife to pay Zakat to her husband.\ 6-\ It is permissible to pay Zakat to relatives as brothers, uncles and cousins, provided\ that\ he\ is\ not required to pay their expenses and he does not inherit from them, as long as they in need.\ 7-\ It is permissible to pay off a debt of dead person from Zakat if the debt was taken for a licit reason.\ 8-\ It is not permissible for a creditor to drop off his debts that owed upon his poor insolvent debtor and count it as a Zakat.\ 9-\ It is not permissible to pay Zakat in ways that prescribed as good deeds which draw closer to God, as buying sacrifices, paying due atonement, or paying the expenses of the Hajj, as well as not permissible to pay Zakat in the cost of the reception of guests and banquets.\ 10-\ Participate in the payment of blood money or in marriage's assistance from Zakat, is mentioned in detail in the research.\ 11-\ Paying Zakat in the charity works is mentioned in detail in the research.\ 12-\ It is not permissible to deduct tax, coupons of irregularities, and a premium of insurance from Zakat.\ 13-\ People engaged in a collection and distribution of Zakat in the present time who belonging to charity associations that authorized by the government, are considered as Zakat's employees who mentioned in the Surat at-Taubah in the verse of people of Zakat. And those given from Zakat, but with conditions listed in the research. This rule includes men and women in the most correct scholarly opinion, but they should not be paid salary from a government.\ And Allah knows best
Keywords: القوانين والتشريعات -- أموال الزكاة -- الاخلاق الاسلامية -- الجمعيات الخيرية -- تحصيل الزكاة -- النظام المالي في الاسلام -- الاقتصاد الاسلامي